Assessment of the acoustic change in heat-treated Pinus elliottii and Bertholletia excelsa wood from homogeneous plantations in Brazil. Issue 4 (20th December 2022) - de Jesus, Daiana Sousa; Castro, Jonnys Paz; Guedes, Taiane; da Silva, José Reinaldo Moreira; Latorraca, João Vicente de Figueiredo; Nascimento, Alexandre Miguel do
Abstract : Heat treatment has been used in wood to improve its technological properties, but due to the complex nature of wood, it is necessary to carry out analyses to confirm the changes, and also to investigate which temperatures and protocols are ideal to provide the desired effect. Thus, this work aimed to evaluate the modulus of elasticity, in order to understand the mechanical behaviour of thermally modified wood, using the non-destructive technique of ultrasound. The subjects of study were the woods of Bertholletia excelsa Bonpl. and Pinus elliottii Engelm. Heat treatments were carried out with temperatures of 160, 180 and 200 °C, for a period of 60 min. After the treatments, the dynamic modulus of elasticity was estimated by the non-destructive technique of ultrasound and the static modulus of elasticity was obtained using a universal testing machine. It was observed that the heat treatment provided an increase in the dynamic modulus of elasticity for both species. For P. elliottii wood, a high linear correlation was observed between the dynamic and static modulus of elasticity for ( R 2 = 0.87). For B. excelsa wood, a low correlation was observed ( R 2 = 0.31).